Examining the Multilevel Barriers and Facilitators to Iron Folic Acid Supplement Use and Anemia Reduction in Rural India (OR25-07-19). (13th June 2019) - Sedlander, Erica; Rimal, Rajiv; Long, Michael; Munjral, Ashita; Yilma, Hagere; Talegawkar, Sameera; Mohanty, Satya
Abstract: Objectives: Over half of women of reproductive age in India are anemic so the World Health Organization recommends daily iron folic acid (IFA) for all women of reproductive age. The government has distributed free IFA for over four decades but initial uptake and adherence remain inadequate. Objectives: 1) to understand the multilevel factors that hinder IFA use and adherence; and 2) to inform a behavioral intervention to increase IFA use to reduce anemia. Methods: We conducted this study in four rural villages in the state of Odisha, India. We held 25 key informant interviews with front-line health workers, 16 focus groups with women of reproductive age, husbands, and mothers-in-law ( n = 148) and 18 direct observations in health centers, pharmacies and women's groups. We purposively sampled key informants and randomly sampled focus group participants from an enumeration of all eligible residents of each village, and stratified them by sex, age and relation to a woman of reproductive age. We analyzed the data using applied thematic analysis and Nvivo software. Results: At the individual level, we found that most people knew that IFA prevents anemia, but they did not recognize its widespread prevalence, believing instead that it was rare in their community. They also believed that taking too many IFA supplements during pregnancy would "make your baby big" causing a painful birth and possibly the need for a cesarean section. At the interpersonal level, mothers-in-law were not supportive of their daughters-in-law taking IFA too often because they themselves did not take them when they were younger. Husbands were more supportive. At the policy level, frontline health workers distribute IFA but are not incentivized to follow up on adherence. Finally, state and national policies are not consistent around which sub-populations should take IFA (e.g., whether all non-pregnant women of reproductive age should take them). Conclusions: To address these multilevel barriers to IFA use and adherence, interventions should take a normative approach that includes a woman's social network and targets both descriptive norms (ideas about how many women in the community have anemia and are taking IFA) and injunctive norms around who should be taking IFA (e.g., all women of reproductive age). Funding Sources: The Bill and Melinda Gates Foundation. Supporting Tables, Images and/or Graphs: